Molybdenum and nickel doped main grid silver paste for photovoltaic cell and preparation method thereof
By adding molybdenum powder and nickel powder to the main gate silver paste of photovoltaic cells, the problems of electrode density and welding performance after sintering are solved, and the amount of silver powder and the production cost are reduced, while the conductivity and welding performance are improved.
Patent Information
- Application Number
- CN202510101312.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-22
AI Technical Summary
After the silver paste of the main gate of the existing photovoltaic cell is replaced by base metal, it is difficult to maintain the density of the electrode after sintering and good welding performance.
The main gate silver paste doped with molybdenum and nickel is used to adjust the sintering matching between the silver powder and the molybdenum powder by adding molybdenum powder to the silver powder to form a dense and poreless electrode.
It significantly reduces the amount of silver powder, reduces production costs, and improves the conductivity and welding performance of low-silver content silver paste, ensuring the reliability and high efficiency of photovoltaic cells.
Smart Images

Figure CN119811744A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic materials, and in particular relates to a main grid silver paste doped with molybdenum and nickel for photovoltaic cells and a preparation method thereof. Background Art
[0002] With the rapid development of the photovoltaic industry, the demand for high-efficiency and low-cost solar cell modules is increasing. As a key material in the manufacturing process of solar cells, the cost of silver paste accounts for an important part of the non-silicon cost of the cell, and silver powder is the top production cost of photovoltaic silver paste. Therefore, photovoltaic silver paste with low silver content and excellent performance has become the focus of the industry.
[0003] Base metal replacement is an important direction in existing technical solutions, but it also faces various problems. For example, aluminum powder has a large particle size and is difficult to adapt to fine-line printing. It is also very easy to oxidize and does not have good solderability. Copper powder is easily oxidized and has poor conductivity, which can easily cause battery short circuits. The silver-coated base metal solution is complex in production and is not suitable for high-temperature fast-firing processes, which limits its application.
[0004] For the silver paste of photovoltaic cell main grid, after replacing silver powder with base metal, it is crucial to maintain the density of the electrode and good welding performance after sintering. Summary of the invention
[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0006] In order to achieve these purposes and other advantages of the present invention, a main grid silver paste doped with molybdenum and nickel for photovoltaic cells is provided, which comprises the following components in parts by weight: 60 to 75 parts of silver powder, 5 to 10 parts of molybdenum powder, 3 to 8 parts of nickel powder, 1 to 5 parts of low softening temperature glass powder, and 20 to 40 parts of organic carrier.
[0007] The present invention also provides a method for preparing a main grid silver paste doped with molybdenum and nickel for a photovoltaic cell, comprising the following steps:
[0008] Step 1: Weigh silver powder, molybdenum powder, nickel powder and glass powder according to proportion and place them in a three-dimensional powder mixer and mix for 2 to 10 hours until all the powders are evenly mixed;
[0009] Step 2: Transfer the evenly mixed powder to the organic carrier weighed in the corresponding proportion, and continue stirring for 2 to 10 hours until the mixture is evenly mixed;
[0010] Step 3: Grind the mixture using a three-roll mill until a silver paste with a fineness that meets the requirements is obtained.
[0011] Preferably, the molybdenum powder is spherical or nearly spherical, with a purity greater than 99.9%, and D50 is controlled at 0.5-2 μm, and the nickel powder should be spherical or nearly spherical, with a purity greater than 99.9%, and D50 is controlled at 1-2 μm.
[0012] Preferably, the softening temperature of the low softening temperature glass powder is 550°C to 650°C, D50 is controlled at 0.5 to 2 μm, and the low softening temperature glass powder contains: in parts by weight, 2 to 10 parts of Bi2O3, 2 to 10 parts of PbO, 20 to 30 parts of CuO, 10 to 30 parts of SiO2, 10 to 20 parts of TiO2, 10 to 20 parts of B2O3, 0 to 10 parts of CaO, and 0 to 10 parts of MgO.
[0013] Preferably, the organic vehicle comprises 15 to 20 parts of a binder, 0 to 2 parts of a thixotropic agent and 80 to 85 parts of an organic solvent.
[0014] Preferably, the binder is one or more of ethyl cellulose, nitrocellulose, cellulose acetate butyrate, acrylic resin, polymethyl methacrylate, and epoxy resin; the thixotropic agent is one or more of polyamide wax and hydrogenated castor oil; and the organic solvent is one or more of diethylene glycol butyl ether acetate, 2,2,2-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,2-trimethyl-1,3-pentanediol diisobutyrate, terpineol, 1-methoxy-2-propanol, dimethyl phthalate, and diethylene glycol dibutyl ether.
[0015] The present invention has at least the following beneficial effects:
[0016] (1) The present invention replaces silver powder by adding molybdenum powder and nickel powder, thereby reducing the amount of silver powder used and significantly reducing the production cost; the preparation method is simple and feasible, and is suitable for large-scale industrial production;
[0017] (2) The present invention makes the low-silver content silver paste have high electrical conductivity and good welding performance by mixing different raw materials;
[0018] (3) The present invention uses nickel powder to adjust the sintering matching between silver powder and molybdenum powder, so that the sintered electrode is dense and free of holes, has good conductivity, and has good welding performance, thereby significantly reducing the silver content while ensuring the reliability and high efficiency of the photovoltaic cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the electrode morphology of the silver paste prepared in Example 1 of the present invention after high-temperature sintering;
[0020] Figure 2 This is the electrode morphology after high-temperature sintering in Comparative Example 1, in which no nickel powder is added but only molybdenum powder is added to the silver paste;
[0021] Figure 3 This is the electrode morphology after high-temperature sintering in Comparative Example 2, in which no molybdenum powder is added but only nickel powder is added to the silver paste;
[0022] Figure 4 This is the electrode morphology of the silver paste of comparative example 3 without adding molybdenum powder and nickel powder after high-temperature sintering. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0024] Example 1
[0025] A method for preparing a main grid silver paste doped with molybdenum and nickel for a photovoltaic cell comprises the following steps:
[0026] Step 1: Weigh 65g of silver powder, 7g of molybdenum powder, 5g of nickel powder, and 3g of low softening temperature glass powder in proportion, place them in a three-dimensional powder mixer and mix for 3 hours until all the powders are evenly mixed; wherein, the composition of the raw materials for preparing the low softening temperature glass powder is: 6gBi2O3, 6g PbO, 25g CuO, 20g SiO2, 15g TiO2, and 15g B2O3.
[0027] Step 2: Transfer the evenly mixed powder to 30 g of an organic carrier and continue stirring for 4 hours until the mixture is evenly mixed; wherein the organic carrier includes a binder: 5.7 g of ethyl cellulose, a thixotropic agent: 0.3 g of polyamide wax, and an organic solvent: 24 g of diethylene glycol butyl ether acetate.
[0028] Step 3: Grind the mixture using a three-roll mill until the fineness of the obtained silver paste reaches D50<2μm.
[0029] The photovoltaic silver paste was printed on a solar cell. An ultra-depth-of-field microscope was used to observe that there were no obvious holes on the electrode surface. The photoelectric conversion efficiency was tested to be above 26.05%, and the welding tensile force was 3.4N. Figure 1 The electrode morphology of the silver paste prepared in this embodiment after high-temperature sintering shows that there are basically no holes on the electrode surface.
[0030] Example 2
[0031] A method for preparing a main grid silver paste doped with molybdenum and nickel for a photovoltaic cell comprises the following steps:
[0032] Step 1. Weigh 70g silver powder, 6g molybdenum powder, 4g nickel powder, and 4g low softening temperature glass powder in proportion, place them in a three-dimensional powder mixer and mix for 3 hours until all the powders are evenly mixed; wherein the composition of the raw materials for preparing the low softening temperature glass powder is: 8g Bi2O3, 8g PbO, 28g CuO, 25g SiO2, 18g TiO2, 12g B2O3, and 5g CaO.
[0033] Step 2: Transfer the evenly mixed powder to 25 g of an organic carrier and continue stirring for 5 hours until evenly mixed; wherein the organic carrier includes a binder: 4 g of nitrocellulose, a thixotropic agent: 0.5 g of hydrogenated castor oil, and an organic solvent: 20.5 g of 2,2,2-trimethyl-1,3-pentanediol monoisobutyrate.
[0034] Step 3: Grind the mixture using a three-roll mill until the fineness of the obtained silver paste reaches D50<1.5μm.
[0035] The photovoltaic silver paste was printed on a solar cell, and an ultra-depth-of-field microscope was used to observe that there were no obvious holes on the electrode surface. The photoelectric conversion efficiency was tested to be above 26.35%, and the welding tensile force was 3.5N.
[0036] Example 3
[0037] A method for preparing a main grid silver paste doped with molybdenum and nickel for a photovoltaic cell comprises the following steps:
[0038] Step 1. Weigh 72g of silver powder, 5g of molybdenum powder, 3g of nickel powder, and 2g of low softening temperature glass powder in proportion, place them in a three-dimensional powder mixer and mix for 3 hours until all the powders are evenly mixed; wherein the composition of the raw materials for preparing the low softening temperature glass powder is: 5gBi2O3, 5g PbO, 22g CuO, 22g SiO2, 16g TiO2, 16g B2O3, and 4g CaO.
[0039] Step 2: Transfer the evenly mixed powder to 28 g of an organic carrier, and continue stirring for 3.5 hours until evenly mixed; wherein the organic carrier includes a binder: 5.32 g of acrylic resin, a thixotropic agent: 0.28 g of polyamide wax, and an organic solvent: 22.4 g of pine alcohol.
[0040] Step 3: Grind the mixture using a three-roll mill until the fineness of the obtained silver paste reaches D50<1μm.
[0041] The photovoltaic silver paste was printed on a solar cell, and an ultra-depth-of-field microscope was used to observe that there were no obvious holes on the electrode surface. The photoelectric conversion efficiency was tested to be above 26.44%, and the welding tensile force was 3.4N.
[0042] Comparative Example 1
[0043] The difference between this comparative example and Example 1 is that nickel powder is not added in step 1, and the silver paste composition is 70g silver powder (the mass of the unadded nickel powder is added to the silver powder to keep the total amount unchanged), 7g molybdenum powder, and 3g low softening temperature glass powder. The remaining steps are uniformly consistent with Example 1. The final silver paste with only molybdenum powder added has an electrode morphology after high-temperature sintering as shown in the figure below. Figure 2 As shown in the figure, it can be observed that there are many large holes on the electrode surface. When only molybdenum powder is added in the high-temperature fast-firing process, the molybdenum powder and silver diffuse very quickly, which easily produces Kendall holes, resulting in loose electrodes and affecting the efficiency and welding tension of photovoltaic cells.
[0044] Comparative Example 2
[0045] The difference between this comparative example and Example 1 is that no molybdenum powder is added in step 1, and the silver paste composition is 72g silver powder (the mass of the unadded molybdenum powder is added to the silver powder to keep the total amount unchanged), 5g nickel powder, and 3g low softening temperature glass powder. The remaining steps are the same as Example 1. The final silver paste with only nickel powder added has an electrode morphology after high temperature sintering as shown in the figure below. Figure 3 As shown, it can be observed that there are many black protrusions on the electrode surface, which is caused by the poor solubility between nickel powder and silver powder.
[0046] Comparative Example 3
[0047] The difference between this comparative example and Example 1 is that the silver paste component is 78g silver powder (the mass of the unadded nickel powder and molybdenum powder is added to the silver powder to keep the total amount unchanged), 3g low softening temperature glass powder, and the remaining steps are uniformly consistent with Example 1. The final silver paste with only silver powder added has an electrode morphology after high temperature sintering as shown in the figure below: Figure 4 As shown, it can be observed that the electrode surface is flat and has no abnormalities.
[0048] The silver paste prepared in Example 1-3 and Comparative Example 1-3 was matched with the same fine grid paste, and silicon solar cells were made under the same printing and sintering conditions. The photoelectric conversion efficiency was tested using an IV tester, and the morphology of the main grid after sintering was tested using an ultra-depth of field microscope. The test results are shown in Table 1 below:
[0049] Table 1: Performance tests of Examples 1-3 and Comparative Examples 1-3
[0050] Silver dosage / g Photoelectric conversion efficiency / % Tension / N Morphology Example 1 65 26.05 3.4 The electrode surface is basically free of holes Example 2 70 26.35 3.5 The electrode surface is basically free of holes Example 3 72 26.44 3.4 The electrode surface is basically free of holes Comparative Example 1 70 25.03 1.6 There are many large holes on the electrode surface Comparative Example 2 72 25.97 1.2 There are many black protrusions on the electrode surface Comparative Example 3 78 26.12 3.6 No holes on the electrode surface
[0051] It can be seen from the test results in the above table that in Examples 1-3, due to the addition of molybdenum powder and nickel powder, in the silver paste system, within a certain range, when an appropriate amount of molybdenum powder is added to replace part of the silver powder, and a good synergistic effect is formed with the nickel powder, the microstructure of the silver paste can be optimized, and the electron transmission path can be smoother, thereby improving the electrical conductivity of the silver paste; at the same time, adding an appropriate amount of molybdenum powder can change the surface properties and internal structure of the silver paste after high-temperature sintering, improve the welding performance of the silver paste, and make the electrode prepared by the silver paste and the external welding material more tightly combined; reasonably controlled amounts of molybdenum powder and nickel powder added can effectively improve the density of the silver paste during sintering, make the sintered electrode dense and free of holes, thereby improving the photoelectric conversion efficiency and reliability of the battery, so the silver paste finally prepared in Examples 1-3 is printed on a solar cell, the electrode surface is smooth, basically free of holes, and also has a higher photoelectric conversion efficiency and welding tension. Compared with Example 1, in Comparative Example 1, since only molybdenum powder is added, the molybdenum powder and silver diffuse very quickly in the high-temperature fast-firing process, and Kendall holes are easily generated, resulting in loose electrodes, affecting the efficiency and welding tension of the photovoltaic cell; in Comparative Example 2, only nickel powder is added, and the co-solubility between nickel powder and silver powder is poor. The nickel powder agglomerates on the electrode surface to form obvious protrusions, which makes it extremely difficult to weld, resulting in low tension; in Comparative Example 3, neither molybdenum powder nor nickel powder is added. Compared with Example 1, although the photoelectric conversion efficiency, tension and battery surface morphology are similar to those of Example 1, due to the reduction in the amount of silver powder used in Example 1, the cost of Example 1 will be significantly reduced, and the cost of Comparative Example 3 is higher.
[0052] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A main grid silver paste doped with molybdenum and nickel for photovoltaic cells, characterized in that: The invention comprises the following components in parts by weight: 60 to 75 parts of silver powder, 5 to 10 parts of molybdenum powder, 3 to 8 parts of nickel powder, 1 to 5 parts of low softening temperature glass powder and 20 to 40 parts of organic carrier.
2. A method for preparing a main grid silver paste doped with molybdenum and nickel for photovoltaic cells as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Weigh silver powder, molybdenum powder, nickel powder and glass powder according to proportion and place them in a three-dimensional powder mixer and mix for 2 to 10 hours until all the powders are evenly mixed; Step 2: Transfer the evenly mixed powder to the weighed organic carrier of the corresponding proportion, and continue stirring for 2 to 10 hours until the mixture is evenly mixed; Step 3: Grind the mixture using a three-roll mill until a silver paste with a fineness that meets the requirements is obtained.
3. The method for preparing the main grid silver paste doped with molybdenum and nickel for photovoltaic cells according to claim 2, characterized in that: The molybdenum powder is spherical or nearly spherical, with a purity greater than 99.9% and a D50 controlled at 0.5-2 μm. The nickel powder should be spherical or nearly spherical, with a purity greater than 99.9% and a D50 controlled at 1-2 μm.
4. The method for preparing a main grid silver paste doped with molybdenum and nickel for photovoltaic cells according to claim 2, characterized in that: The softening temperature of the low softening temperature glass powder is 550℃~650℃, and D50 is controlled at 0.5~2μm. The low softening temperature glass powder contains: in parts by weight, 2~10 parts of Bi2O3, 2~10 parts of PbO, 20~30 parts of CuO, 10~30 parts of SiO2, 10~20 parts of TiO2, 10~20 parts of B2O3, 0~10 parts of CaO, and 0~10 parts of MgO.
5. The method for preparing the main grid silver paste doped with molybdenum and nickel for photovoltaic cells according to claim 2, characterized in that: The organic carrier comprises 15 to 20 parts of a binder, 0 to 2 parts of a thixotropic agent and 80 to 85 parts of an organic solvent.
6. The method for preparing the main grid silver paste doped with molybdenum and nickel for photovoltaic cells according to claim 5, characterized in that: The binder is one or more of ethyl cellulose, nitrocellulose, cellulose acetate butyrate, acrylic resin, polymethyl methacrylate, and epoxy resin; the thixotropic agent is one or more of polyamide wax and hydrogenated castor oil; the organic solvent is one or more of diethylene glycol butyl ether acetate, 2,2,2-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,2-trimethyl-1,3-pentanediol diisobutyrate, pineneol, 1-methoxy-2-propanol, dimethyl phthalate, and diethylene glycol dibutyl ether.
Citation Information
Patent Citations
Solar cell back face silver paste and preparing method thereof
CN104575669A
Positive silver paste and preparation method thereof
CN107068241A
All-aluminum BSF (back surface field) back electrode slurry and preparation method and application thereof
CN110120274A
Composition for solar cell electrodes and electrode fabricated using the same
US20150291811A1